Trygve Lie, the Palestine Question, and International Loyalty - HABIBY, RAYMOND (Dirasat in Economics and Business, 1980)
The records of the United Nations and the writings and statements of Trygve Lie, first secretary General of the U.N. show that Lie played a major role in the U.N. decision making process, the day the Palestine case was first placed on the agenda of the international body by Britain in 1947 in its capacity as the mandatory power, until he resigned from the U.N. The role he played significantly influenced those member states which on November 29, 1947, in the General Assembly, voted to adopt the partition of Palestine and the internationalization of Jerusalem. This paper tries to determine whether Lie as Secretary General acted within the limits of the powers he possessed either expressly or implicitly under the United Nations charter, and whether his many initiatives in the Palestine Question and the leadership roles he played were in accordance with the concepts of loyalty, integrity, and impartiality expected and required from an international civil servant.